SOCIAL SCIENCE GRADUATE EMPLOYABILITY AND ENGLISH LANGUAGE PROFICIENCY: FINDINGS FROM A PUBLIC UNIVERSITY IN MALAYSIA - Esther Jawing; Kamsilawati Kamlun (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Recent literature suggested that the English language proficiency appears to influence graduates’ employability in the job market especially in the South-East Asia context. This study investigated the Social Science graduates’ employability in relation to the English Language proficiency in a Malaysian public university. A quantitative research design was utilised and involved 7025 graduates from the 2015, 2016 and 2017 graduating years. Three variables were examined consisting of the graduates’ employment status, the English Language course results, and Malaysian University English Test (MUET) results. These data were analysed using descriptive statistics and Chi Square test. Findings showed inconsistent trends of unemployed graduates in this three-year period albeit a notable increase in 2016. The chi-square analysis suggested that there was an association between the English language proficiency and social science graduates’ employability. Although the English language proficiency is highlighted as the contributing factor to graduates’ employability, this study concluded that the mismatch between the students’ perceptions and the employers’ expectations should be addressed. It is further recommended that an ecosystem of key players in the industry and universities should be developed to constantly address the issues related to graduates’ employability upon graduation.